2013
DOI: 10.5902/1984686x10070
|View full text |Cite
|
Sign up to set email alerts
|

A inclusão de crianças com Transtornos do Espectro do Autismo nas escolas públicas dos Estados Unidos

Abstract: Legislation in the United States mandates that all children with disabilities (including those with autism spectrum disorder) have access to the general education curriculum in the least restrictive environment. Although a number of benefits associated with including children with autism spectrum disorder (ASD) in settings with their typically developing peers have been documented in the literature, skepticism remains regarding the ability of general education teachers to fully address the myriad of challenges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…In fact, research is limited regarding the central purpose of inclusive settings for students with ASD (Falkmer et al, 2015;Ferraioli & Harris, 2011). The lack of published research may actually lead to contradictions and lack of clear direction for professionals (Crosland & Dunlap, 2012;Dunlap, Iovannone, & Kincaid, 2008;Whalon & Hanline, 2013). Falkmer et al (2015) discuss several of the contradictions currently indicated in research regarding inclusion for students with ASD.…”
Section: Lack Of Researchmentioning
confidence: 99%
“…In fact, research is limited regarding the central purpose of inclusive settings for students with ASD (Falkmer et al, 2015;Ferraioli & Harris, 2011). The lack of published research may actually lead to contradictions and lack of clear direction for professionals (Crosland & Dunlap, 2012;Dunlap, Iovannone, & Kincaid, 2008;Whalon & Hanline, 2013). Falkmer et al (2015) discuss several of the contradictions currently indicated in research regarding inclusion for students with ASD.…”
Section: Lack Of Researchmentioning
confidence: 99%